The particularities of senior pupils’ professional self-determination at up-to-date world. - Revenko, G. О.; Shostakovych-Koretska, L. R.; Мasvrutenkov, V. V.; Budayeva, І. V.; Galushenko, S. А.; Kovaliova, Т. М.; Zhukovtsova, А. G.; Svechnikova, О. L. (Medicni Perspektivi, 2015)
The aim of the work was assaying motivational aspects of seniorpupils’ career guidance. Today the emotional focus of young people is pragmatic: material and personal well-being, the ability to survive in modern society, profitable employment, meetingwell-to-do life partner, "having good sponsors," " rich patron", "avoidingarmy service".Civil loadings such as service of the country and society aren’t appreciated. The lack of sufficiently deep professional orientation of graduates does not preclude its formation during pariod of training at higher educational institutions. Therefore, the task of the school (family and community) consists in choosingof profession which is logical consequence of gradually increasing professional orientation. To solve these problems, first of all, it is necessaryto conduct systematic vocational guidance at schools, starting to gradually introduce children into the world of professions beginning with middle classes.